A systematic study on immiscible binary systems undergoing thermal/photo reversible chemical reactions. Issue 3 (13th December 2022) - Li, Changhao; Li, Jianfeng; Zhang, Hongdong; Yang, Yuliang
Abstract : Numerical simulations show that the wavelength of the light-induced dissipative patterns depends on the input energy density. Abstract : In this work, we systematically study an immiscible binary system undergoing thermal/photo reversible reactions in theory. For the thermal reaction case, no dissipative structures can be formed and only uniform equilibrium states are observed but the dynamical evolution to these trivial states witnesses a new type of sophisticated phase amplification phenomenon—temporary phase separation (TPS). Linear analysis and light-scattering calculations confirm that TPS is predominated either by spinodal decomposition or nucleation and growth mechanism, or by both successively. For the photo reaction case, steady dissipative patterns exist and are maintained by the external energy input of lights. Linear analysis together with simulations reveals that the characteristic wavelength ( ξ ) of these structures shortens as the input energy density increases and they obey the relation of ln  ξ ∝ 1/ T b with T b the effective temperature of lights. The TPS phenomenon and length-scale dependency of dissipative patterns observed in this simple binary system might have rich implications for the non-equilibrium thermodynamics of biological systems.